Isaac Kalimi, The Book of Esther between Judaism and Christianity. The Biblical Story, Self-identification and Antisemitic Interpretation. - De Troyer , Kristin (Antiguo Oriente, 2025)
This is an excellent book, and a must read for all scholars interested in the book of Esther and its reception history, especially the antisemitic story and its far-reaching consequences.